Bee pollen supplementation in diets for rabbit does and growing rabbits - doi: 10.4025/actascianimsci.v35i4.18950 - Daisa Mirelle Borges Dias; Maria Cristina de Oliveira; Diones Montes da Silva; Nadielli Pereira Bonifácio; Daniel da Cunha Claro; Wilson Aparecido Marchesin (Acta Scientiarum. Animal Sciences, 2013)
It was evaluated the effects of bee pollen (BP) on the doe and kits productivity and on thecarcass and organs of the rabbits. Twenty White New Zealand does and their kits were used in arandomized block design, with four treatments and five blocks, in a factorial arrangement 2 x 2 with twosupplementation levels for the doe and for the kits after the weaning. BP supplementation for the does didnot influence (p > 0.05) the doe and kit productivity during the lactation, except by the kits survival rate(p < 0.003), the total (p < 0.002) and daily (p < 0.001) milk production that increased in supplementeddoe. BP supplementation for the doe and/or kits did not affect (p > 0.05) the rabbit performance from theweaning until the slaughter age, the slaughter weight, carcass characteristics, except by the spleen and smallintestine weights, higher in supplemented rabbits. It was not recommended that BP supplementation fordoes and/or rabbits for not improving the rabbit productive performance